Time-varying shock transmission in non-Gaussian structural vector autoregressions - Helmut Lütkepohl; Till Strohsal (Deutsches Institut für Wirtschaftsforschung (DIW), 2025)
This paper analyzes possibly time-varying shock transmission in structural vector autoregressive (VAR) models when the reduced-form VAR coefficients are time-invariant and the shocks are identified through non-Gaussianity. To check for possible time-variation in the impulse responses, we propose Wald tests for two situations: (1) homoskedastic and (2) heteroskedastic structural shocks. For the latter case, the challenge is to ensure that the test does not indicate time-varying impulse responses if the changes are due only to changes in the variances of the shocks. To illustrate the usefulness of the tests, they are applied to an empirical model of the crude oil market. They support time-varying shock transmission reflected in impulse response functions that change over time.
Keywords: C32; 330; Structural vector autoregression; independent component analysis; non-Gaussian shocks; structural break tests; heteroskedasticity